Sectoral capacities need strengthening to deliver sufficient tree seed for forest and landscape restoration - Jalonen, Riina; Vinceti, Barbara; Gaisberger, Hannes; Thomas, Evert; Ekue, Marius; De Ridder, Benjamin; Besacier, Christophe; Kettle, Christopher J. (Food and Agriculture Organization of the United Nations, 2023)
The quality and origin of tree seeds and seedlings affect the survival, growth, productivity, ecosystem services and adaptive capacity of restored forests and landscapes. The availability of seeds and seedlings directly influences the delivery of benefits to land users from restoration efforts. Yet, despite more than a decade of global restoration commitments and programmes since 2011, substantial gaps remain worldwide in individual, organizational and sectoral capacities to source and deliver quality tree seeds and seedlings for restoration, especially of native species. Data from global surveys indicate that these gaps affect many, if not most, ongoing projects and result in delays in implementation, cost increases and suboptimal restoration outcomes.